2008
DOI: 10.3732/ajb.95.3.299
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic traits are influenced by phylogenetic history in the drought‐resistant, invasive genus Juniperus (Cupressaceae)

Abstract: In the conifer genus Juniperus (Cupressaceae), many species are increasing rapidly in distribution, abundance, and dominance in arid and semiarid regions. To help understand the success of junipers in drier habitats, we studied hydraulic traits associated with their water stress resistance, including vulnerability to xylem cavitation, specific conductivity (K(S)), tracheid diameter, conduit reinforcement, and wood density in stems and roots, as well as specific leaf area (SLA) of 14 species from the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
130
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 72 publications
(168 reference statements)
11
130
3
Order By: Relevance
“…In studies of other lineages, traits related to plant water relations have shown a wide range of phylogenetic lability, but hydraulics traits have tended to be conservative (Cavender-Bares et al 2004, Preston et al 2006. Indeed, K s and K l were among the few traits in this study with a relatively high degree of ''phylogenetic inertia,'' consistent with the finding that traits related to stem hydraulic architecture were strongly influenced by the phylogenetic history (Hao et al 2008, Willson et al 2008. The controlling effect of hydraulic conductivity over photosynthetic capacity has been well studied across diverse species sets (Brodribb and Field 2000, Melcher et al 2001, Brodribb et al 2002, Santiago et al 2004a, b, Franks 2006, Zhang and Cao 2009).…”
Section: Phylogenetic Signal and Correlated Evolution Of Functional Tsupporting
confidence: 77%
See 1 more Smart Citation
“…In studies of other lineages, traits related to plant water relations have shown a wide range of phylogenetic lability, but hydraulics traits have tended to be conservative (Cavender-Bares et al 2004, Preston et al 2006. Indeed, K s and K l were among the few traits in this study with a relatively high degree of ''phylogenetic inertia,'' consistent with the finding that traits related to stem hydraulic architecture were strongly influenced by the phylogenetic history (Hao et al 2008, Willson et al 2008. The controlling effect of hydraulic conductivity over photosynthetic capacity has been well studied across diverse species sets (Brodribb and Field 2000, Melcher et al 2001, Brodribb et al 2002, Santiago et al 2004a, b, Franks 2006, Zhang and Cao 2009).…”
Section: Phylogenetic Signal and Correlated Evolution Of Functional Tsupporting
confidence: 77%
“…5A). A large divergence among lineages, coupled with reduced divergence within lineages can cause ahistorical correlations to diminish substantially when analyzed using phylogenetic independent methods (Willson et al 2008). On the other hand, traits with a higher degree of homoplasy usually show less discrepancy between ahistorical and PIC correlations.…”
Section: Phylogenetic Signal and Correlated Evolution Of Functional Tmentioning
confidence: 99%
“…in Texas (Archer 1995), ponderosa pine (Pinus ponderosa P.&C. Lawson) in the Black Hills of South Dakota (Shinneman and Baker 1997), and eastern red cedar (Juniperus virginiana, L.), which can be found in every state east of the 100 th meridian (McKinley andBlair 2008, Starks et al 2014), encroaching into 7 million ha of grasslands, shrublands, and riparian forests in the Great Plains, along a precipitation gradient ranging from semiarid in its western distribution (Eggemeyer et al 2009) to mesic in its eastern distribution (Willson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As for cell anatomical characteristics, the two sites exhibited similar cell anatomy, likely due to a strong genetic control of tracheid dimension (Willson et al 2008). Although we observed some clear differences between the sites and among the climatic years, earlywood tracheids, which represented about 85% to 91% of the cells in the ring, showed lower LD/CWT values at the drier site (SA) than at the more mesic 4.94* Note: Data refer to eight trees (13 radii) in Peña Lampa (LA) and six trees (10 radii) in Santa Engracia (SA).…”
Section: Prp'iojs "Ear Current Year | |Gjevi0ustew| Current Yearmentioning
confidence: 99%